The relationship between marketing mix towards customer satisfaction: a case study at Mydin Mall Kuala Terengganu / Nurul Nadiah Syafawati Mohd Alim - Mohd Alim, Nurul Nadiah Syafawati (2014)
The aim for this research is to identify whether there is the relationship between the Principle of Marketing Mix (4Ps) and Customer Satisfaction. The research will be done at Mydin Mall Kuala Terengganu. I am choosing to do this research is because I feel customers will choose to shop at certain supermarkets due to their satisfaction level. For this research, I prepared a set of questionnaires to be asked to the Mydin Mall customers to know their satisfaction level. The result of the research will be used to identify which variables will influence to the satisfaction level of customers.